2010
DOI: 10.1002/eqe.992
|View full text |Cite
|
Sign up to set email alerts
|

Application of MPA to estimate probability of collapse of structures

Abstract: This paper develops a modal pushover analysis-(MPA) based approximate procedure to quantify the collapse potential of structural systems. The computationally demanding incremental dynamic analysis (IDA) of the structural system is avoided by MPA of the structure in conjunction with empirical equations for the collapse strength ratio for the first-mode single-degree-of-freedom (SDF) system; higher modes of vibration play essentially no role in estimating the ground motion intensity required to cause collapse of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…Since modal combination is valid only for combining modal displacement demands not for modal force demands, total collapse strength (A c ) cannot be computed by modal combination of A c for each mode. However, Han et al [21] showed that collapse strength considering only the first mode is sufficiently accurate since the higher mode contribution becomes smaller as ground motion intensity increases. Moreover, Vamvatsikos and Cornell [7] reported that with accumulating damage in the structure, some of the dominant frequencies seem to be "silenced" and the structure becomes more first-mode dominated.…”
Section: Mpa-based Ida With Empirical Equations Of C R and R Cmentioning
confidence: 98%
See 2 more Smart Citations
“…Since modal combination is valid only for combining modal displacement demands not for modal force demands, total collapse strength (A c ) cannot be computed by modal combination of A c for each mode. However, Han et al [21] showed that collapse strength considering only the first mode is sufficiently accurate since the higher mode contribution becomes smaller as ground motion intensity increases. Moreover, Vamvatsikos and Cornell [7] reported that with accumulating damage in the structure, some of the dominant frequencies seem to be "silenced" and the structure becomes more first-mode dominated.…”
Section: Mpa-based Ida With Empirical Equations Of C R and R Cmentioning
confidence: 98%
“…Han et al [6,21] reported that the MPA based IDA with the strength-limited bilinear model provided accurate prediction of seismic demands and capacities for regular steel moment resisting frames. The effect of structural and hysteretic properties on C R is to be investigated through comprehensive statistical study.…”
Section: Mpa-based Ida With Empirical Equations Of C R and R Cmentioning
confidence: 99%
See 1 more Smart Citation
“…These include typical code-suggested fits, e.g., as laid out in Eurocode 8 [11], FEMA-356 [12], ASCE/SEI 41-06 [13], and the Italian Code (Circolare 617/2009, [18]). In addition several bilinear, trilinear and quadrilinear fits, including solutions available in literature [15,16,20], have been investigated. Different fitting criteria, e.g., varying initial stiffness, yield point definition, and softening slope, have been employed in an attempt to pinpoint the consistent characteristics that can define an optimal or near-optimal fit.…”
Section: Exact Versus Approximate Sdof Systemsmentioning
confidence: 99%
“…using a 10% rule with areaminimization for the hardening segment that terminates at the peak strength. To determine the softening segment, which extends from the peak point to the ultimate, three different approaches are considered: (a) the first, termed secant, employs the slope linking the peak point with the ultimate; (b) the second, termed Han et al, which follows the graphical approach suggested in [20], provides as softening slope the bisector between the peak-to-ultimate point slope and the slope at the end of the backbone; (c) the third, termed balanced, uses areaminimization to fit the descending segment, utilizing a negative slope and, at times, a horizontal residual strength segment. The latter is only added when it can help achieve a closer fit, typically being needed for steep-mild cases.…”
Section: Multilinear Fits Of Generalized Elastic-hardening-negative Smentioning
confidence: 99%